IMPLEMENTATION OF WORK ACTIVITIES FOR PRISONERS IN STRENGTHENING LOCUS OF CONTROL IN METRO CLASS IIA CORRECTIONAL INSTITUTION - Salma, Aliya; Soge, Markus Marselinus (Universitas Nusa Cendana, 2026)
This study aims to analyze the implementation of work activity programs for inmates at the Metro Class IIA Correctional Institution in supporting the main objective of the correctional system, namely social reintegration. These work activities are designed to equip inmates with practical skills and increase their motivation to improve their quality of life by strengthening their internal locus of control (LoC). The research uses a qualitative descriptive approach, with data collected through interviews, observations, and document analysis. The study applies program implementation theory and Locus of Control theory to understand how the program is carried out and its impact on inmates. The findings show that the implementation of work activities has been supported by collaboration with external partners and active participation from inmates who engage in activities based on their interests and talents. This condition helps strengthen inmates’ internal locus of control, as they become more responsible, confident, and motivated to plan their future after release. However, several challenges still hinder the optimal implementation of the program, including limited product marketing, low motivation among some inmates, budget constraints, and limited access to training. Therefore, improvements are needed, particularly in expanding marketing strategies, increasing training opportunities, and strengthening institutional support, so that the program can more effectively contribute to inmates’ personal development and successful social reintegration. Keywords: Correctional Institution; Locus of Control, Prisoners; Work Activities